Catchment-to-intake-point economic valuation of water resources using a hybrid method - Abdul Hamid Mar Iman (Universiti Malaysia Kelantan, 2016)
Catchment-to-intake-point (CTIP) economic valuation of water resources is an important aspect of sustainable forest management. With a total of about 94,851 ha of forest catchment area, the state of Johor has among the largest inland water bodies and, thus, water resources in Malaysia. However, the economic valuation of CTIP water resources is rather undeveloped in this country. This paper introduces a hybrid method of CTIP economic valuation of water resources from forest catchment areas based on state-wide Cobb-Douglas translog production function and residual methods, by taking the state of Johor, Malaysia, as a case study. Data on Gross Domestic Product (GDP), labour (L), capital (K), water (W), energy (E), and raw materials (M) were collected for the state of Johor from various secondary sources. Using a pro-rata price in 2014, the total value of CTIP water resources for an assumed lease period of 60 years at 4% per annum is RM 70,272,825.14. This is equivalent to the use-value of water of RM 1,171,213.75 per annum which is an additional source of income to the state government.